Flavonoids in Lemon and Grapefruit IntegroPectin. Issue 10 (27th October 2021) - Scurria, Antonino; Sciortino, Marzia; Albanese, Lorenzo; Nuzzo, Domenico; Zabini, Federica; Meneguzzo, Francesco; Alduina, Rosa; Presentato, Alessandro; Pagliaro, Mario; Avellone, Giuseppe; Ciriminna, Rosaria
Abstract: Following the analysis of terpenes present in new lemon and grapefruit "IntegroPectin" pectins obtained via the hydrodynamic cavitation of industrial lemon and grapefruit processing waste, the HPLC‐MS analysis of flavonoid and other phenolic compounds reveals the presence of eriocitrin, naringin, hesperidin and kaempferol typical of the respective citrus fruits. The pectic fibers rich in rhamnogalacturonan‐I regions act as chemical sponges adsorbing and concentrating at their outer surface highly bioactive citrus flavonoids and terpenes. These findings, together with the unique molecular structure of these new whole citrus pectins, provide preliminary insight into the broad‐scope biological activity of these new biomaterials. Numerous new biomedical applications are anticipated, including likely use in the prevention and treatment of microbial infections and neurodegenerative disease. Abstract : Molecular synergy in action, IntegroPectin ! The pectic fibers rich in rhamnogalacturonan‐I regions of lemon and grapefruit "IntegroPectin" pectins obtained via the hydrodynamic cavitation of industrial lemon and grapefruit processing waste, adsorb and concentrate at their outer surface highly bioactive citrus flavonoids and terpenes. Flavonoid compounds include eriocitrin, naringin, hesperidin and kaempferol typical of the respective citrus fruits.